Benefits of preparing for childbirth with mindfulness training: a randomized controlled trial with active comparison - Larissa G. Duncan; Michael A. Cohn; Maria T. Chao; Joseph G. Cook; Jane Riccobono; Nancy Bardacke (BMC, 2017)
Abstract Background Childbirth fear is linked with lower labor pain tolerance and worse postpartum adjustment. Empirically validated childbirth preparation options are lacking for pregnant women facing this problem. Mindfulness approaches, now widely disseminated, can alleviate symptoms of both chronic and acute pain and improve psychological adjustment, suggesting potential benefit when applied to childbirth education. Methods This study﻿, the Prenatal Education About Reducing Labor Stress (PEARLS) study, is a randomized controlled trial (RCT; n = 30) of a short, time-intensive, 2.5-day mindfulness-based childbirth preparation course offered as a weekend workshop﻿, the Mind in Labor (MIL): Working with Pain in Childbirth, based on Mindfulness-Based Childbirth and Parenting (MBCP) education.﻿ First-time mothers in the late 3rd trimester of pregnancy were randomized to attend either the MIL course or a standard childbirth preparation course with no mind-body focus. Participants completed self-report assessments pre-intervention, post-intervention, and post-birth, and medical record data were collected. Results In a demographically diverse sample, this small RCT demonstrated mindfulness-based childbirth education improved women's childbirth-related appraisals and psychological functioning in comparison to standard childbirth education. MIL program participants showed greater childbirth self-efficacy and mindful body awareness (but no changes in dispositional mindfulness), lower post-course depression symptoms that were maintained through postpartum follow-up, and a trend toward a lower rate of opioid analgesia use in labor. They did not, however, retrospectively report lower perceived labor pain or use epidural less frequently than controls. Conclusions This study suggests mindfulness training carefully tailored to address fear and pain of childbirth may lead to important maternal mental health benefits, including improvements in childbirth-related appraisals ﻿and﻿ the prevention of postpartum depression symptoms. There is also some indication that MIL participants may use mindfulness coping in lieu of systemic opioid pain medication. A large-scale RCT that captures real-time pain perceptions during labor and length of labor is warranted to provide a more definitive test of these effects. Trial registration The ClinicalTrials.gov identifier for the PEARLS  study is: NCT02327559 . The study was retrospectively registered on June 23, 2014.